O comportamento de consumo de serviços de entretenimento noturno: uma abordagem sobre o gênero feminino - Guilherme Barbosa de Carvalho (2003)
The study of consumer behavior is considered by many important authors as one of the most important subjets in the study of marketing. Moreover, in the development of marketing strategies, the knowledge about consumer behavior is considered essential by these authors.Therefore, in competitive markets, these knowledge assumes considerable importance. As an exemple, entertainment services in Belo Horizonte can be considered an important area to be explored. The female students of universities in Belo Horizonte can still be considered an important segment since they represent almost sixty percent of the students in the southwest of the contry. Since the study of consumer behavior and the decision processes involved starts with the needs recognition, this thesis tries to describe the decision processes of the young female students in Belo Horizonte to buy entertainment services at night. This study still tries to propose a priority scale of needs when these young women search entertainment services at night in the city.